IL4‐10 fusion protein: a novel immunoregulatory drug combining activities of interleukin 4 and interleukin 10. (11th November 2018) - Steen‐Louws, C.; Hartgring, S. A. Y.; Popov‐Celeketic, J.; Lopes, A. P.; de Smet, M. B. M.; Eijkelkamp, N.; Lafeber, F. P. J. G.; Hack, C. E.; van Roon, J. A. G.
Summary: The objective of this study was to test the capacity of a newly developed fusion protein of interleukin 4 (IL‐4) and IL‐10 [IL4‐10 fusion protein (FP)] to shift multiple pro‐inflammatory pathways towards immune regulation, and to inhibit pro‐inflammatory activity in arthritis models. The effects of IL4‐10 FP in comparison with IL‐4, IL‐10 and IL‐4 plus IL‐10 on pro‐ and anti‐inflammatory mediators, T cells and immunoglobulin (Ig) receptors in favour of immunoregulatory activity were studied. In addition, the capacity of IL4‐10 FP to inhibit pro‐inflammatory activity in ex‐vivo and in‐vivo arthritis models was investigated. IL4‐10 FP robustly inhibited pro‐inflammatory cytokine [IL‐1β, tumour necrosis factor (TNF)‐α, IL‐6 and IL‐8] production in whole blood cultures, mediated by both the IL‐10 and the IL‐4 moiety. IL4‐10 fusion protein induced IL‐1 receptor antagonist (IL‐1RA) production and preserved soluble TNF receptor (sTNFR) levels, strongly increasing IL‐1RA/IL‐1β and sTNFR/TNF‐α ratios. In addition, IL4‐10 FP strongly inhibited T helper (Th) type 1 and 17 cytokine secretion, while maintaining FoxP3 expression and up‐regulating Th2 activity. In addition, while largely leaving expression of activating Fc gamma receptor (FcγR)I, III and Fc epsilon receptor (FcεR) unaffected, it significantly shifted the FcγRIIa/FcγRIIb ratio in favour of the inhibitory FcγRIIb. Moreover, IL4–10 FP robustly inhibited secretion of pro‐inflammatory cytokines by rheumatoid arthritis synovial tissue and suppressed experimental arthritis in mice, without inducing B cell hyperactivity. IL4‐10 fusion protein is a novel drug, signalling cells to induce immunoregulatory activity that overcomes limitations of IL‐4 and IL‐10 stand‐alone therapy, and therefore has therapeutic potential for inflammatory diseases such as rheumatoid arthritis. Abstract : IL4‐10 fusion protein (IL4–10 FP) combines two potent anti‐inflammatory cytokines with unique properties into one molecule. IL4‐10 FP signals cells to induce robust immunoregulatory activity, strongly inhibiting pro‐inflammatory cytokine production by RA synovial tissue explants and suppressing experimental arthritis in mice. IL4‐10 fusion protein overcomes limitations of IL‐4 and IL‐10 stand‐alone therapy and therefore has therapeutic potential for the treatment of inflammatory diseases.